ANALISIS RISIKO BERBAGAI LUAS PENGUSAHAAN LAHAN PADA USAHATANI PADI ORGANIK DAN KONVENSIONAL - Tinjung Mary Prihtanti (Fakultas Pertanian dan Bisnis, Universitas Kristen Satya Wacana, 2014)
This study aims to identify the production risk and return risk of organic and conventional wetland rice farm, based on farming area, at Pereng, Mojogedang, Karanganyar regency, and Sukorejo, Sambirejo, Sragen regency. Data were collected by interviewing 37 organic farmers and 80 conventional farmers. The result showed that the coefficient of variance of production and return of organic rice farm was lower than conventional’s; suggesting that the risk of organic farm was lower than the latter.